2006
DOI: 10.1111/j.1600-0838.2006.00610_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical aftermath of amateur boxing

Abstract: BACKGROUND: Little solid information is available on the possible risks for neuronal injury in amateur boxing. OBJECTIVE: To determine whether amateur boxing and severity of hits are associated with elevated levels of biochemical markers for neuronal injury in cerebrospinal fluid. DESIGN: Longitudinal study. SETTING: Referral center specializing in evaluation of neurodegenerative disorders. PARTICIPANTS: Fourteen amateur boxers (11 men and three women) and 10 healthy male nonathletic control subjects. INT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
101
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 0 publications
8
101
0
1
Order By: Relevance
“…Zetterberg et al (2006) examined cerebrospinal fluid (CSF) taken by from lumbar puncture in 14 amateur boxers 7 to 10 days and 3 months after a bout compared to matched controls without any contact. They used several markers of neuronal and astroglial injury that can be readily detected in the CSF, finding significant indicators of neuronal injury byproducts in CSF that were positively related to the actual number of hits during a bout, most apparent in the initial samples taken after the amateur boxing contest.…”
Section: Pathophysiology Of Concussionmentioning
confidence: 99%
“…Zetterberg et al (2006) examined cerebrospinal fluid (CSF) taken by from lumbar puncture in 14 amateur boxers 7 to 10 days and 3 months after a bout compared to matched controls without any contact. They used several markers of neuronal and astroglial injury that can be readily detected in the CSF, finding significant indicators of neuronal injury byproducts in CSF that were positively related to the actual number of hits during a bout, most apparent in the initial samples taken after the amateur boxing contest.…”
Section: Pathophysiology Of Concussionmentioning
confidence: 99%
“…Patients with stroke initially have increased T-tau levels, which normalize after a few months (Hesse et al 2001). In amateur boxers, head trauma leads to increased T-tau levels, which normalize after a few months of rest (Zetterberg et al 2006). In patients treated with electroconvulsive therapy, T-tau levels are stable after up to six treatment sessions, indicating that such treatment does not induce neuronal damage (Zachrisson et al 2000).…”
Section: Amyloid Markersmentioning
confidence: 99%
“…148 Studies have demonstrated that the ratio of CSF to serum albumin can be used as a means to detect disruption of the BBB in severe brain injury; however, these results were not replicated in cases of mTBI. 15,29,67,147 Tau protein and neurofilaments have emerged as biomarker candidates for axonal injury in CSF because these molecules represent the pathognomonic features found in neurodegenerative diseases, including CTE. Two prospective studies, consisting of 30 and 14 amateur boxers, compared levels of neurofilament light protein and total tau in the CSF to nonboxing healthy controls.…”
mentioning
confidence: 99%